Ikaw ang big time! ang komodipikasyon ng pagkakataon sa programang Wil Time Big Time - Sayo, Chastine Joy Sison^d1991- (2012.)
"This undergraduate thesis delves on how chance is commodified in Wil Time Big Time. It aims to explain how chance is packaged and sold in Wil Time Big Time and how it is consumed by its audiences. Enough data were acquired from watching five episodes of the program, two weeks and fieldwork and interviews with Wil Productions and with those who line-up to join the contest. Studies show that out country is facing an economic crisis and any way to answer people's needs are very much welcome. Wil Time Big Time, then, is considered to be one answer to these needs. Majority of Filipino believe in luck and with the opportunities provided by the program. Wil Time Big Time affirms and supports ths belief that anyone has a chance to be lucky. With this in mind, having a chance is very crucial for the reason that it opens door for good luck. Based on the data collected, there is commodification and marketization of chance among the masses. The institution commodifies and commercializes chance through categories and a set of criteria as a 'flicker of hope' for success, a chance in audition, in articipation even in winning in the game. Chance is also sold whenever the audience experience pleasure by watching, participating and dreaming or aspiring to have it. Having said this, chance becomes a commodity that is valued as a promise for a comfortable and successful life. Moreover, these chances are sellable because it is the aspiration of society. This trend will continuously happen as long as there is economic crisis in the country because poor Filipinos will continue to rely on the promises given by these game shows. Having said this, the researcher suggests that media literacy should be enriched to revise the creation of game shows and promote a responsible media that fosters substantial television."
Vita.
Thesis (A. B. in Broadcast Communication)--University of the Philippines, Diliman.
Keywords: Wil Time Big Time (Television game show).; Television game shows -- Philippines; Commodification -- Philippines